2022
DOI: 10.1177/10998004221104850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic, Resistance, and Combined Exercise Training on Depressive Symptoms, Quality of Life, and Muscle Strength in Healthy Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background Aerobic training, resistance training, or combined training are interventions that can be modified to suit the needs of aged people. Objective This meta-analysis aimed to investigate the impact of exercise training on depression symptoms, quality of life, and muscle strength in healthy people aged 60 or more. Data Sources Searches were conducted in PubMed, Web of Science, Medline, Google Scholar, and Scopus databases from inception to February 2022. Results Eighteen studies, totaling 1354 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…Subsequently, a systematic review and meta-analysis involving eighteen randomized controlled trials investigated the impact of aerobic, resistance, and combined training on depressive symptoms among healthy older adults. The findings revealed that each of these exercise interventions showed potential for improving depressive symptoms [54]. Also, a study on the benefits of the same three exercise protocols on the mental health-related quality of life in hypothyroid women found that the combined exercise achieved the greatest benefits, with the aerobic and resistance protocols both obtaining similar values [16].…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, a systematic review and meta-analysis involving eighteen randomized controlled trials investigated the impact of aerobic, resistance, and combined training on depressive symptoms among healthy older adults. The findings revealed that each of these exercise interventions showed potential for improving depressive symptoms [54]. Also, a study on the benefits of the same three exercise protocols on the mental health-related quality of life in hypothyroid women found that the combined exercise achieved the greatest benefits, with the aerobic and resistance protocols both obtaining similar values [16].…”
Section: Discussionmentioning
confidence: 92%
“…Among all participants, five individuals had a score below 50 before the pilgrimage that increased to above 50 in each participant after the pilgrimage, i.e., the patients benefited considerably from the intervention. Many studies have already shown that exercise can positively affect mood and well-being [ 17 , 18 , 19 ]. However, a systematic review has shown that results about the effects of exercise training on quality of life and mental well-being in people with type 2 diabetes are conflicting [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the associations between changes in depressed mood and physical activity of ≥60 min or high-intensity physical activity were not significant; however, the rate of increased depressed mood after the COVID-19 pandemic in relation to muscle-strengthening exercises decreased after adjusting for pre-existing depression. In a previous study comparing the effects of aerobic and muscle-strengthening exercises on depression in adults, both aerobic and muscle-strengthening exercises, regardless of sex, significantly reduced feelings of depression [ 23 ]. A study targeting showed that both aerobic and anaerobic exercises had significant effects on reducing depression and that anaerobic exercise had a more significant effect on strengthening self-concept compared to aerobic exercise [ 24 ].…”
Section: Discussionmentioning
confidence: 99%